Hydrogen-induced plasticity in nanoporous palladium - Gößler, Markus; Steyskal, Eva-Maria; Stütz, Markus; Enzinger, Norbert; Würschum, Roland (Beilstein Journal of Nanotechnology, 2018)
The mechanical strain response of nanoporous palladium (npPd) upon electrochemical hydrogenation using an in situ dilatometric technique is investigated. NpPd with an average ligament diameter of approximately 20 nm is produced via electrochemical dealloying. A hydrogen-induced phase transition from PdHβ to PdHα is found to enable internal-stress plasticity (or transformation-mismatch plasticity) in nanoporous palladium, which leads to exceptionally high strains without fracture as a result of external forces. The high surface stress in the nanoporous structure in combination with the internal-stress plasticity mechanism leads to a peculiar strain response upon hydrogen sorption and desorption. Critical potentials for the formation of PdHα and PdHβ in npPd are determined. The theoretical concepts to assess the plastic strain response of nanoporous samples are elucidated, taking into account characteristics of structure and deformation mechanism.
Keywords: electrochemistry; hydride formation; in situ dilatometry; internal-stress plasticity; nanoporous palladium